The autistic children social problems in the male and female teachers’ point of view At Al-Nourain and Al-Rajaa Institutes A field social study in Al-Diwaniyah city - Hassan Sadkhan Al-Badri, Hana (International Journal of Psychosocial Rehabilitation, 2020)
The autistic behavior of children is unclear and complex, and often it is not possible to know why the concerned child behaves with a specific behavior and what the aim of this behavior is. The reason for this is that the child cannot express what is inside or what he needs naturally which it differs from that on natural behavior and knowledge of the characteristics and general symptoms of autistic children is very important which helps in diagnosis and treatment and thus rehabilitation, there are psychological, mental and social characteristics of the autistic children that parents know through direct dealing with the autistic child, but because of the lack of knowledge of the reality of autism and the lack of the treatment that eliminates the symptoms, most parents pay not to accept that their child has autism through diagnosis or what drives them to rely on teachers through their behavior with their peers in the institutions for autistic children, as this affects the psychological and social conditions of the children themselves and their guardians, because they are considered an important source of diagnosis and identification of the general characteristics of the autistic child. Therefore, the lack of acceptance of this matter (the diagnosis of their child because he is autistic) leads to a delay in the rehabilitation and training process, in addition to the suffering of both parties (the child and his family). It is therefore important to obtain an early diagnosis to overcome some difficulties and avoid pain for both parties. This study, through observing the autistic children at Al-Nourain and Al-Rajaa Institutes in the city of Diwaniya, has reached several results, most notably: Most autistic children suffer from mental disorders and problems, and among these problems are excessive movement, mocking and ridicule of their colleagues, and hearing problems. The hearing problems greatly affect the communication process between the children and the teachers, as it involves them. In most cases, the child’s behavior with his teacher is calm. The research consisted of two chapters; the first chapter was the theoretical side and included three topics: the first topic dealt with defining the concepts, terms, and main elements of the research, which are represented by the research problem and the importance of the research and the goals of the research, while the second topic dealt with the problems faced by children with autism, while the third topic dealt with the causes of autism, while the fourth topic included methods of autism treatment, as the fifth topic included the types and characteristics of autism. As for the second chapter, the field side contained three topics. The sixth topic included the research methodology, research sample, research fields, and statistical means. As for the seventh topic, it dealt with analysis and tabulation of data, while the eighth topic included results and recommendations, then the sources, and from God the best.